2017
DOI: 10.18632/oncotarget.18420
|View full text |Cite
|
Sign up to set email alerts
|

Melflufen - a peptidase-potentiated alkylating agent in clinical trials

Abstract: Aminopeptidases like aminopeptidase N (APN, also known as CD13) play an important role not only in normal cellular functioning but also in the development of cancer, including processes like tumor cell invasion, differentiation, proliferation, apoptosis, motility, and angiogenesis. An increased expression of APN has been described in several types of human malignancies, especially those characterized by fast-growing and aggressive phenotypes, suggesting APN as a potential therapeutic target.Melphalan flufenami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 37 publications
0
111
0
Order By: Relevance
“…We also demonstrated that knock down of CD13 in D492HER2 cells reduced the efficacy of melflufen further demonstrating the importance of CD13 for the activity of melflufen in D492HER2 cells. The efficient activity of melflufen in cancer cells has been documented in several articles (reviewed in 21 ). Chauhan et al demonstrated that melflufen was highly efficient in killing myeloma cells, even cells that had acquired resistance to melphalan.…”
Section: F I G U R E 5 In Vivo Effects Ofmentioning
confidence: 99%
“…We also demonstrated that knock down of CD13 in D492HER2 cells reduced the efficacy of melflufen further demonstrating the importance of CD13 for the activity of melflufen in D492HER2 cells. The efficient activity of melflufen in cancer cells has been documented in several articles (reviewed in 21 ). Chauhan et al demonstrated that melflufen was highly efficient in killing myeloma cells, even cells that had acquired resistance to melphalan.…”
Section: F I G U R E 5 In Vivo Effects Ofmentioning
confidence: 99%
“…Melflufen is a PDC that is being investigated in multiple myeloma and other hematologic malignancies, immunoglobulin light chain (AL) amyloidosis, and solid tumors [ 29 , 33 , 34 ].…”
Section: Preclinical Developmentmentioning
confidence: 99%
“…Melflufen is highly lipophilic, which promotes its rapid uptake by cells [ 29 , 30 , 31 , 35 ] ( Figure 1 ). Once within the cell, melflufen releases its hydrophilic alkylator payloads via the hydrolytic activity of intracellular peptidases (e.g., aminopeptidases) [ 30 ].…”
Section: Preclinical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Melflufen is newer generation alkylator therapy and a modified derivative of one of the oldest MM therapies, melphalan. Melflufen is activated by aminopeptidases and its metabolites are more lipophilic than melphalan, allowing better transport across cell membranes . Recent phase II data from the HORIZON Trial of melflufen plus dexamethasone in RRMM reported 33% overall response rate (ORR) and 4 months PFS among 82 evaluable patients.…”
Section: Emerging Clinical Trialsmentioning
confidence: 99%